2014
DOI: 10.1177/1359104514547596
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of implementing shared decision making in Child and Adolescent Mental Health Services in the United Kingdom: Stages and facilitators

Abstract: Implementation of SDM in CAMHS is effortful, and while tools may help support SDM, clinicians need to be allowed to use the tools flexibly to allow them to move from a state of apprehension through a sense of feeling "clunky" to integration in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 18 publications
(25 reference statements)
1
52
0
2
Order By: Relevance
“…This finding may suggest that goal formulation and tracking may be associated with higher levels of parental satisfaction, potentially through higher levels of parental involvement and collaborative working, as suggested by prior research [2, 42], and may highlight the association between therapeutic relationships and the importance of goal formulation and tracking [12, 16, 20, 27, 55, 61, 65]. It may of course also be possible that this association is more to do with another common factor such as greater therapeutic alliance to which both higher levels of goals and satisfaction relate, but given the existing literature on how goal setting might help support this it is not unreasonable to at least consider goal setting as enhancing satisfaction and collaborative working.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…This finding may suggest that goal formulation and tracking may be associated with higher levels of parental satisfaction, potentially through higher levels of parental involvement and collaborative working, as suggested by prior research [2, 42], and may highlight the association between therapeutic relationships and the importance of goal formulation and tracking [12, 16, 20, 27, 55, 61, 65]. It may of course also be possible that this association is more to do with another common factor such as greater therapeutic alliance to which both higher levels of goals and satisfaction relate, but given the existing literature on how goal setting might help support this it is not unreasonable to at least consider goal setting as enhancing satisfaction and collaborative working.…”
Section: Discussionmentioning
confidence: 52%
“…Because naturalistic research is a measure of everyday life, participants may not have the commitment they might have had to providing data in a randomised control trial. Moreover, the practice of goal formulation can feel strange to practitioners and has, as part of collaborative practice, been described as feeling ‘clunky’ [2] perhaps especially when the approach has not been implemented in a well-considered manner, such as having open discussions and training [67]. Parents who are less satisfied may be more likely to disengage and not provide outcome or feedback information [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest of the studies were carried out in Australia ( n = 2), Hong Kong ( n = 1) and Canada ( n = 1). In terms of the aims of included studies, eight studies primarily focused on exploring experiences and beliefs related to PCC ( n = 2; Abrines‐Jaume et al, ; Grealish, Tai, Hunter, & Morrison, ), whereas other studies looked into various aspects of service users' general experience of mental health services.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, all studies but one (Molesworth & Crome, ) presented findings in a comprehensive manner providing quotes illustrating the main themes obtained by the analysis. Nonetheless, several studies did not provide sufficient detail on issues such as justification of the research design ( n = 3; Iachini, Hock, Thomas, & Clone, ; Molesworth & Crome, ; Street, ), recruitment strategy ( n = 6; Lee et al, ; LeFrançois, ; Ma & Lai, ; Molesworth & Crome, ; Offord, Turner, & Cooper, ; Street, ), data collection ( n = 3; LeFrançois, ; Molesworth & Crome, ; Street, ), the relationship between researcher and participants ( n = 14; Buckley et al, ; Harper, Dickson, & Bramwell, ; Hart, Saunders, & Thomas, ; Iachini et al, ; Kovshoff et al, ; Lee et al, ; LeFrançois, ; Molesworth & Crome, ; Offord et al, ; Oruche, Downs, Holloway, Draucker, & Aalsma, ; Pelto‐Piri, Engstrom, K., & Engstrom, ; Street, ; Tam‐Seto & Versnel, ; Wisdom, Clarke, & Green, ), ethical issues ( n = 4; Abrines‐Jaume et al, ; LeFrançois, ; Molesworth & Crome, ; Wisdom et al, ) and rigour of data analysis ( n = 4; Hart et al, ; LeFrançois, ; Molesworth & Crome, ; Street, ). Finally, contribution to research, knowledge or policy was not discussed in two studies (Molesworth & Crome, ; Street, ), new areas of research were not identified in six studies (Buckley et al, ; Hart et al, ; Lee et al, ; Molesworth & Crome, ; Pycroft, Wallis, Bigg, & Webster, ; Street, ) and generalizability of findings was not taken into account in nine studies (Buckley et al, ; Bury, Raval, & Lyon, ; Coyne et al, ; Kovshoff et al, ; LeFrançois, ; Molesworth & Crome, ; Offord et al, ; Pelto‐Piri et al, ; Street, …”
Section: Resultsmentioning
confidence: 99%